Determination of oxidative stress in common carp (Cyprinus carpio) treated with phenol - Tasci, Didem; Yonar, Muhammet Enis (Ege Univ, Fac Fisheries, 2025)
This study examined the effects of phenol exposure on oxidative stress and antioxidant defense mechanisms in common carp (Cyprinus carpio). A total of 120 common carp with an average body mass of 30 g were randomly allocated into four experimental sets, consisting of one untreated control and three groups subjected to phenol at 0.01, 0.1, and 1 ppm for 96 hours. Following the exposure period, samples of liver and gill tissues were obtained to assess oxidative stress markers, including malondialdehyde (MDA), and the enzymatic activities of catalase (CAT), glutathione peroxidase (GSH-Px), glutathione Stransferase (GST), along with reduced glutathione (GSH) levels. The analysis revealed that MDA concentrations were markedly elevated in every group exposed to phenol relative to the control fish, demonstrating enhanced lipid peroxidation and heightened oxidative stress. Antioxidant enzyme activities (CAT and GSH-Px) and GSH levels significantly decreased in liver and gill tissues, while GST activity increased in a dose-dependent manner. These findings suggest that phenol disrupts the balance between oxidation and antioxidant defences, leading to cellular stress and potential tissue damage. The changes in enzyme activity imply compensatory mechanisms or detoxification responses triggered by phenol exposure. Since even low concentrations of phenol caused notable oxidative changes, this study highlights its potential toxicity to aquatic organisms. The results emphasize the importance of cautious use of phenolic compounds in aquatic environments and contribute to a broader understanding of phenol-induced oxidative stress in fish. Further research involving different species, exposure durations, and physiological markers is recommended to confirm and expand these findings.
Keywords: Antioxidants; fish; phenols; oxidative stress